Evaluasi Kebijakan Penanggulangan Kemiskinan di Kecamatan Suruh, Kabupaten Semarang - Kamil, M. Ghulam; Artiningsih, Artiningsih (Jurusan Perencanaan Wilayah dan Kota, 2024)
Development aims to fulfill social and economic needs for the citizen reaching the welfare. poverty becomes one of the problem which the world pays attention much on it. indonesia, as one of the developing countries, recently, is facing this problem. many policies related to poverty have been implemented which is intended to decrease the amount of citizen with low economic level. however, the policies haven’t made any significant effects, one of the example is in the suruh district, semarang region. semarang regency, which is one of the supporting area of the capital city of central java, geographically gains advantages to reach the optimum level of welfare, somehow turns to be the opposite. the goal of this research is to acknowledge the effective policies that are related to poverty countermeasures in suruh district. methods that are being used are descriptive method and checklist method. policies that are being used in this research is Semarang Regency’s RKPD 2022